Pengembangan Prosedur Haccp Food Safety dengan Metode Design Thinking - Muhammad Ervinza; Irhamsyah Pulungan; Asep Taryana Sujana (Syntax Corporation Indonesia, 2024)
An overview of important aspects of food safety in the restaurant industry by outlining the significant threat of microbial contamination in food processing and the subsequent health implications that can arise from foodborne illness. This article underscores the need for strict management and hygiene practices to mitigate these risks. In addition, it highlights the important role of preventive measures, particularly the adoption of food safety management systems such as HACCP, which play a role in identifying and controlling potential hazards in food production and preparation processes. In addition, the impact of customer feedback can affect a restaurant's reputation and customer satisfaction levels. Overall, it emphasized the importance of routine food safety practices and the proactive role of restaurant management in maintaining public health and maintaining consumer trust.